Obesity paradox in patients undergoing lung lobectomy - myth or reality? - Tulinský, Lubomír; Mitták, Marcel; Tomášková, Hana; Ostruszka, Petr; Penka, Igor; Ihnát, Peter (BMC surgery, 2018)
BACKGROUND: The aim of the present study was to evaluate the impact of BMI on the short-term outcomes of patients undergoing lung lobectomy. METHODS: This was a retrospective clinical cohort study conducted in a single institution to assess the short-term outcomes of obese patients undergoing lung resection. Intraoperative and postoperative parameters were compared between the two study subgroups: obese (BMI ≥30 kg/m2) and non-obese patients (BMI < 30 kg/m2). RESULTS: In total, 203 patients were enrolled in the study (70 obese and 133 non-obese patients). Both study subgroups were comparable with regards to demographics, clinical data and surgical approach (thoracoscopy vs. thoracotomy). The surgery time was significantly longer in obese patients (p = 0.048). There was no difference in the frequency of intraoperative complications between the study subgroups (p = 0.635). The postoperative hospital stay was similar in both study subgroups (p = 0.366). A 30-day postoperative morbidity was higher in a subgroup of non-obese patients (33.8% vs. 21.7%), but the difference was not significant (p = 0.249). In the subgroup of non-obese patients, a higher frequency of mild and severe postoperative complications was observed. However, the differences between the study subgroups were not statistically significant due to the borderline p-value (p = 0.053). The 30-day postoperative mortality was comparable between obese and non-obese patients (p = 0.167). CONCLUSIONS: Obesity does not increase the incidence and severity of intraoperative and postoperative complications after lung lobectomy. Slightly better outcomes in obese patients indicate that obesity paradox might be a reality in patients undergoing lung resection.
Keywords: obezita; délka operace; Humans; torakoskopie; peroperační komplikace; Postoperative morbidity; index tělesné hmotnosti; lidé středního věku; Body Mass Index; Obesity paradox; Female; Aged; Intraoperative Complications; Lung; morbidita; výsledek terapie; senioři; lidé; plíce; Pulmonary lobectomy; Postoperative Complications; Operative Time; pooperační komplikace; ženské pohlaví; Body mass index; Male; Middle Aged; Retrospective Studies; Morbidity; incidence; Incidence; Treatment Outcome; Thoracoscopy; Obesity; retrospektivní studie; mužské pohlaví; Length of Stay; délka pobytu